2016
DOI: 10.1128/aac.01178-16
|View full text |Cite
|
Sign up to set email alerts
|

Bioluminescent Reporters for Rapid Mechanism of Action Assessment in Tuberculosis Drug Discovery

Abstract: cThe tuberculosis (TB) drug discovery pipeline is fueled by compounds identified in whole-cell screens against the causative agent, Mycobacterium tuberculosis. Phenotypic screening enables the selection of molecules that inhibit essential cellular functions in live, intact bacilli grown under a chosen in vitro condition. However, deducing the mechanism of action (MOA), which is important to avoid promiscuous targets, often requires significant biological resources in a lengthy process that risks decoupling med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(73 citation statements)
references
References 53 publications
5
67
1
Order By: Relevance
“…For mechanism of action of these compounds against Mtb, the results obtained from triage assays 53,54 , the lack of hypersensitivity observed in a cydKO mutant, and measurement of OCR eliminate mycobacterial respiration as target. In contrast, the immediate and sustained luminescence signal in the PiniB-LUX reporter assay strongly implicates cell wall homoeostasis as a likely primary target 57 . Moreover, the detection of late-stage (after day 4) triggering of recA promoter activity suggests some effect on DNA metabolism as well.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…For mechanism of action of these compounds against Mtb, the results obtained from triage assays 53,54 , the lack of hypersensitivity observed in a cydKO mutant, and measurement of OCR eliminate mycobacterial respiration as target. In contrast, the immediate and sustained luminescence signal in the PiniB-LUX reporter assay strongly implicates cell wall homoeostasis as a likely primary target 57 . Moreover, the detection of late-stage (after day 4) triggering of recA promoter activity suggests some effect on DNA metabolism as well.…”
Section: Discussionmentioning
confidence: 92%
“…Notably, no significant change in the OCR was observed following treatment with 16, also reinforcing the notion that QcrB is not the primary target (Supplementary Methods and Supplementary Figure 1). Bioluminescence reporter assays 57 were used to establish if the compounds 15-17 disrupt cell wall homoeostasis or are genotoxic in Mtb. All three compounds elicited a strong signal using the PiniB-LUX reporter (Supplementary Figure 2), triggering an immediate luminescence signal on day 1 which was sustained throughout the 10-day assay, as was observed for the isoniazid control.…”
Section: Resultsmentioning
confidence: 99%
“…Fusion of the iniBAC promoter to β‐galactosidase or luciferase results in a strong inducible reporter signal . A bacterial luciferase reporter, generated using the iniBAC promoter, generated a reporter strain that can be used to quickly assess mechanism of action of novel molecules, by identifying compounds that have isoniazid‐like activity and cell wall stress triggering activities . An iniBAC reporter was also used in a genetic screen in Mycobacterium marinum to discover new genes controlling cell wall stress responses.…”
Section: Pathway Specific Transcriptional Reportersmentioning
confidence: 99%
“…S6). We focused on induction of the iniBAC operon, which is rapidly upregulated due inhibition of cell-wall synthesis and is used to screen for cell-wall acting compounds (12, 13). We observed that cycloserine’s induction of iniBAC genes was mild compared to other cell-wall acting antibiotics (~1.5 fold and ~3.5 fold respectively), consistent with the weak association of cycloserine to other cell-wall antibacterials (Figure 3 Right and Fig S6 Top).…”
Section: Resultsmentioning
confidence: 99%